Correlates of Protection Against SIVmac251 Infection in Rhesus Macaques Immunized With Chimpanzee-Derived Adenovirus Vectors - Steven Tuyishime; Larissa H. Haut; Raj K. Kurupati; James M. Billingsley; Diane Carnathan; Sailaja Gangahara; Tiffany M. Styles; ZhiQuan Xiang; Yan Li; Malte Zopfs; Qin Liu; XiangYang Zhou; et al. (EBioMedicine, 2018)
We report on prime-boost vaccine regimens with two simian adenovirus (Ad) vectors (SAdV) or two human serotype Ad vectors (HAdV) expressing Gag and gp160 of simian immunodeficiency virus (SIV)mac239 tested in HAdV-seropositive rhesus macaques (RMs) repeatedly challenged rectally with low doses of SIVmac251. Both vaccine regimens reduced set point and peak viral loads (PVL) and accelerated viral clearance. In SAdV-vaccinated controller genotype RMs resistance against infection correlated with levels of envelope (Env)-specific antibody (Ab) titers. In both vaccine groups CD8+T cells controlled viral loads (VL) upon infection. Circulating CD4+ and CD8+ T cells showed significant changes in their transcriptome over time following vaccination, which differed between the vaccine groups. T cells from SIV-resistant RMs had unique transcriptional profiles indicating that both follicular T helper (TFH) cell responses and highly activated CD8+ T cells may play a role in protection. Keywords: HIV-1 vaccine, Adenovirus vector, Mucosal challenge, Protection, Gene expression profiles